REMOCIÓN DE SEMILLAS DE CHILCO (Henriettella fissanthera) EN EL PARQUE TINIGUA: FACTORES QUE INFLUYEN EN EL TIEMPO DE VISITA - Stevenson, Pablo R.; Department of Anthropology State University of New York at Stony Brook (2013)
The duration of feeding bouts on fruiting trees by animal dispersers may have an effect on seed dispersal effectiveness. In this study we quantified seed removal rates and visit duration for different animal vectors in three trees of Henriettellafissanthera (Melastomataceae). The main purpose was to describe seed removal rates by different dispersers, ánd test the associatiop. of three characteristics of the dipersors that ha ve been proposed to affect bout duration times: crypsis, diet and gut capacity. We observed three primate species and 24 bird species ingesting fruits during a period of 85 h. H. fissanthera fruits correspond to the birdE dispersal syndrome, and they removed the majority of seeds, although primates removed a significant proportion offruits (40%). The largest tree was visited more often than the medium and small trees. Our results indicated that neither crypsis or diet were associated with the average duration of feeding bouts. Probably these results can be explained by the fact that the frugivories are not very exposed to aerial predators when feeding on H. fissanthera fruits, and because particular fruit preferences by frugivories seem to be very important in determining visit times. We found a positive association between average visit time and body weight (as a surrogate variable for gut capacity), but this correlation was not significant, suggesting that other factors may be more important deterrnining the duration of feeding bouts in this plant species ( e.g. instantaneous fruit abundance, tree distribution and interspecific aggressions ).